2014
DOI: 10.1016/s2095-3119(13)60573-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Antioxidant Content and Its Relationship to Grain Color and Morphological Characteristics in Winter Wheat Grains

Abstract: The current interest in the health benefits of whole wheat grain has prompted breeders to further increase the concentration of antioxidants in wheat. The objective of this study was to investigate the variation in antioxidant content among Chinese wheat grains and the relationship between antioxidants and grain color and morphological characteristics. A wide variation was observed in the total phenolic, carotenoid and flavonoid content, as well as the antioxidant activity (AOA), of Chinese wheat varieties. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 34 publications
3
22
0
1
Order By: Relevance
“…Liu et al 28 showed significant differences in total phenolic content of purple, red, yellow and white grain wheat, with the first two colour types grains having the highest antioxidant amounts. The relationship between grain colour and antioxidant content was also reported by Ma et al, 29 who highlighted higher polyphenol, flavonoid and carotenoid content in black and red wheat as compared to white wheat. This is in agreement with our results, which showed a higher phenolic content of red grain varieties over the white ones.…”
Section: Effect Of Genotype and Environment On The Phenolic Contentsupporting
confidence: 75%
“…Liu et al 28 showed significant differences in total phenolic content of purple, red, yellow and white grain wheat, with the first two colour types grains having the highest antioxidant amounts. The relationship between grain colour and antioxidant content was also reported by Ma et al, 29 who highlighted higher polyphenol, flavonoid and carotenoid content in black and red wheat as compared to white wheat. This is in agreement with our results, which showed a higher phenolic content of red grain varieties over the white ones.…”
Section: Effect Of Genotype and Environment On The Phenolic Contentsupporting
confidence: 75%
“…Production of wheat is focused primarily in China, Russia, Turkey, Indian, Ukraine, Australia, United States, and Pakistan, accounting for above 80% of the global wheat production (Ikhtiar and Alam, 2007; Siddiqui and Naz, 2009; Sun et al, 2014). Pakistan is the eighth leading producer of wheat, accounting for almost 3.17% of the wheat output in the world from 3.72% of the area under wheat cultivation (Shuaib et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The recent interest in the benefits of whole cereal grain with respect to health has encouraged breeders to rise the wheat antioxidants concentration (Sun et al, 2014). The aim of this study was to examine the difference in the content of antioxidant among ancient cultivars, land races of wild relatives of domesticated crop, and advance as well as segregating lines of wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Вище ми продемонстрували залежність між виходом і якістю крупи та твердістю зерна. Генетичну варіабельність пшениці за кольором зерна сьогодні розглядають як важливе джерело біофортифікації (збагачення) пшениці такими біологічно цінними складовими зерна, як вітаміни, мінерали й особливо компоненти зерна з антиоксидантною активністю [34].…”
Section: результати та обговоренняunclassified